EMPLOYEE PERFORMANCE IMPROVEMENT INFLUENCED BY PARTICIPATIVE LEADERSHIP, INTERPERSONAL COMMUNICATION AND JOB SATISFACTION AT PT PUTRA WIJAYA KLATEN, CENTRAL JAVA - Novianto Eko Nugroho (Universitas Nahdlatul Ulama Sidoarjo, 2022)
The purpose of this research is to determine and analyze the effect of participative leadership, interpersonal communication, and job satisfaction on employee performance at PT Putra Wijaya, Klaten, Central Java. This research uses causal-comparative research. The research object is the transportation service company PT Putra Wijaya, Klaten, Central Java. Research data were obtained by distributing questionnaires. The population of this research is all employees who work at PT Putra Wijaya, Klaten, Central Java. This research utilizes 77 respondents. The results prove that participative leadership, interpersonal communication, and job satisfaction have a significant effect on employee performance. This research proves a strong influence on job satisfaction.